Endoscopic ultrasound-guided transduodenal drainage of idiopathic retroperitoneal abscess in an immunocompromised patient: A case report. Issue 50 (December 2017) - Sagami, Ryota; Tsuji, Hiroaki; Nishikiori, Hidefumi; Murakami, Kazunari
Abstract: Rationale: Idiopathic retroperitoneal abscesses are insidious, occult illnesses with high mortality if inadequately drained. Endoscopic ultrasound-guided drainage is an alternative to percutaneous or surgical drainage, it is not widely performed for retroperitoneal abscesses other than peripancreatic fluid collection. Patient concerns: We present a 76-year-old Japanese woman with abdominal pain, high fever, and a history of rheumatism on treatment with immunosuppressants. Diagnoses: The patient was diagnosed with idiopathic retroperitoneal abscess based on results obtained from her clinical course and findings on computed tomography. Interventions: We performed Endoscopic ultrasound—guided drainage. After we performed needle puncture via the descending portion of the duodenum, the fistula was expanded using a dilator, and a double-pigtail stent and endoscopic nasobiliary drainage tube were inserted. Outcomes: The patient was kept nil by mouth, together with intravenous antibiotic therapy, and repeated washing of the abscess cavity with saline was performed. After that, we confirmed disappearance of the cavity, and, after removing the tubes, commenced oral feeding. We were able to avoid surgery in this immunosuppressed patient. Lessons: Endoscopic ultrasound (EUS)-guided abscess drainage can be overall considered a safe and useful procedure. We also propose the double-stent method, with both internal and external stents, for the treatment of idiopathic retroperitoneal abscesses.